1973
DOI: 10.1302/0301-620x.55b2.301
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF FLUORINE-18 AND STRONTIUM-87m SCINTIGRAPHY IN THE MANAGEMENT OF INFECTIVE SPONDYLITIS

Abstract: 1. An ancillary diagnostic technique using Fluorine-l8 or Strontium-87m is described, and has assisted in the correct diagnosis of fifty-two patients admitted with the provisional diagnosis of infective spondylitis. 2. The technique is of particular value in the assessment of reactivation of chronic spinal infections and in the differential diagnosis of atypical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Still, this technique may be used in both the diagnosis and the follow-up of pyogenic spondylitis. It is a good indicator with regard to the reactivation of an infectious process (Kemp et al 1973) and roentgenographically dubious primary lesions and recurrences (Fellander & Lindberg 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Still, this technique may be used in both the diagnosis and the follow-up of pyogenic spondylitis. It is a good indicator with regard to the reactivation of an infectious process (Kemp et al 1973) and roentgenographically dubious primary lesions and recurrences (Fellander & Lindberg 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the bone scan viewed in isolation is also poor (13%), rising to 70% when clinical information is taken into account (Sundberg et al 1989). In both adults and children, the uptake of bone-seeking tracers is increased in the third (bone) phase with tuberculous (Kettunen and Rekonen 1968;Kemp et al 1973) and septic arthritis. Infection involving an epiphysis may be photon-deficient acutely if the intramedullary pressure is high enough to impair the blood supply (Garnett et al 1977).…”
Section: Infectionmentioning
confidence: 99%
“…In addition, pyogenic infection of bone has been investigated with intravenous scintigraphy. Because acute epidural spinal abscess is often associated with vertebral infection, the potential value of scintigraphy is sufficient to merit giving it a trial as a diagnostic weapon in spite of the fact that Kemp et al (1973) reported that there was no increased uptake of the intravenous radioactive fluorine and strontium in relation to soft tissue lesions such as paravertebral abscess. 0032-5473/79/1000-0712 $02.00 © 1979 The Fellowship of Postgraduate Medicine Two cases which illustrate the penalties of delays in diagnosis are described.…”
Section: Ancillary Investigationsmentioning
confidence: 99%